2006
DOI: 10.1109/tnsre.2006.875570
|View full text |Cite
|
Sign up to set email alerts
|

ECoG factors underlying multimodal control of a brain-computer interface

Abstract: Most current brain-computer interface (BCI) systems for humans use electroencephalographic activity recorded from the scalp, and may be limited in many ways. Electrocorticography (ECoG) is believed to be a minimally-invasive alternative to electroencephalogram (EEG) for BCI systems, yielding superior signal characteristics that could allow rapid user training and faster communication rates. In addition, our preliminary results suggest that brain regions other than the sensorimotor cortex, such as auditory cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(115 citation statements)
references
References 17 publications
3
104
0
3
Order By: Relevance
“…These human results have since been replicated and further extended for decoding of arm movements (Pistohl et al, 2008;Sanchez et al, 2008), flexion of individual fingers (Kubanek et al, 2007), and even specific aspects (such as the type of phoneme) of actual or imagined speech (Schalk et al, 2007a). Finally, several studies demonstrated that it is possible to combine general understanding of motor-related ECoG responses (Crone et al, 1998a,b;Aoki et al, 1999;Graimann et al, 2002;Sinai et al, 2005;Leuthardt et al, 2007;Miller et al, 2007) with the more specific understanding described above to implement different ECoG-based BCIs (Leuthardt et al, 2004;Wilson et al, 2006;Felton et al, 2007;Schalk et al, 2008) in humans using the BCI2000 software framework . These studies showed that ECoG supports accurate nonmuscular one-or two-dimensional movement control in humans with little subject training.…”
Section: Signal Fidelity Of Ecogmentioning
confidence: 99%
“…These human results have since been replicated and further extended for decoding of arm movements (Pistohl et al, 2008;Sanchez et al, 2008), flexion of individual fingers (Kubanek et al, 2007), and even specific aspects (such as the type of phoneme) of actual or imagined speech (Schalk et al, 2007a). Finally, several studies demonstrated that it is possible to combine general understanding of motor-related ECoG responses (Crone et al, 1998a,b;Aoki et al, 1999;Graimann et al, 2002;Sinai et al, 2005;Leuthardt et al, 2007;Miller et al, 2007) with the more specific understanding described above to implement different ECoG-based BCIs (Leuthardt et al, 2004;Wilson et al, 2006;Felton et al, 2007;Schalk et al, 2008) in humans using the BCI2000 software framework . These studies showed that ECoG supports accurate nonmuscular one-or two-dimensional movement control in humans with little subject training.…”
Section: Signal Fidelity Of Ecogmentioning
confidence: 99%
“…ECoG-based BCIs have controlled 1-or 2-dimensional cursor movements using motor or sensory imagery or working memory (dorsolateral prefrontal cortex). [87][88][89][90][91] An ECoG-based BCI can enable users to control a prosthetic hand or to select characters using motor-imagery or the P300 event-related potential. 12,[92][93][94] Most recently, ECoG signals measured over speech cortex during overt or imag-ined phoneme and word articulation were used for online cursor control 95 and were also accurately decoded off-line for potential application to direct speech synthesis.…”
Section: Bcis That Use Ecog Activitymentioning
confidence: 99%
“…The AI was then determined for each electrode by the feature with the largest normalized change between rest and movement states for all hand movements: (3) The five electrodes with the highest AI values were considered to represent hand movementrelated locations for the purposes of connectivity analysis. Five electrodes were chosen because for all subjects except Subject C, previous work has shown that within five electrodes, decoding accuracy (r, correlation between actual and predicted hand movements) reached approximately 95% of maximum decoding accuracy [12].…”
Section: Ecog Electrode Activation Indexmentioning
confidence: 99%